2014
DOI: 10.1002/pip.2552
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the monolithic interconnection on CIS solar cells by picosecond laser structuring on 30 by 30 cm2 modules

Abstract: In this paper, we present the selective structuring of all three patterns (P1, P2 and P3) of a monolithic interconnection of CIS (Cu(In,Ga)(S,Se) 2 ) thin film solar cells by picosecond laser pulses at a wavelength of 1064 nm. We show results for single pulse ablation threshold values and line scribing of molybdenum films on glass (P1), CIS on molybdenum (P2) and zinc oxide on CIS (P3). The purposes of these processes are the p-type isolation (P1), cell interconnect (P2) and n-type isolation (P3), which are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…By adjusting the laser intensity, beam shape, and incidence direction (Figure d), various groove shapes are obtained, with the corresponding results shown in Figure g. Similar to a previous study, as shown in Figure g1 and g2, a Mo groove with sharp vertical edge can be obtained with configurations of L1 and L2, by an incident scribing laser beam from either the Mo side or the glass side. As reported in the literature, for P2, grooves with a gradual slope instead of an abrupt edge are always preferred to form continuous TCO films to reduce the series resistance .…”
supporting
confidence: 78%
See 1 more Smart Citation
“…By adjusting the laser intensity, beam shape, and incidence direction (Figure d), various groove shapes are obtained, with the corresponding results shown in Figure g. Similar to a previous study, as shown in Figure g1 and g2, a Mo groove with sharp vertical edge can be obtained with configurations of L1 and L2, by an incident scribing laser beam from either the Mo side or the glass side. As reported in the literature, for P2, grooves with a gradual slope instead of an abrupt edge are always preferred to form continuous TCO films to reduce the series resistance .…”
supporting
confidence: 78%
“…Seemingly, P1 is a simple and easy process in the module fabrication process and only requires removal of the back‐contact film (e.g., Mo thin film in CIGS‐based solar devices), where the quality is always assessed by the microscopic images . As a consequence, there is limited information regarding the shape of the P1 groove edge in the region between Mo and glass substrate and its influence on the final CIGS modules.…”
mentioning
confidence: 99%
“…Here, transitioning from ns-pulsed lasers to ps-pulsed lasers for ablation provides advantages, enabling both narrower and more uniform scribing due to reduced thermal effects [1][2][3][4][5]. This also reduces unintended deposition of ablated materials on scribe sidewalls, which unmitigated create shunting pathways [4,5]. Other authors report IC width down to 250 µm using a combination of pulsed-laser and optimized mechanical scribing [6].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical patterning of P2 and P3 is known to create fewer smooth trenches compared to laser ablation [20]. However, scribing P2 and P3 by nanosecond laser ablation is not recommended, as it might also damage the back contact [21]. According to reference [21], structuring of P2 and P3 scribes can be performed with picosecond laser ablation.…”
Section: Methodsmentioning
confidence: 99%